2021
DOI: 10.1097/phm.0000000000001845
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis on the Effectiveness of Transcranial Direct Current Stimulation on Swallowing Function of Poststroke Patients

Abstract: ObjectiveThe purpose of this study was to investigate the therapeutic effects of transcranial direct current stimulation on swallowing function in poststroke patients.DesignWe searched for potentially eligible randomized controlled trials from electronic databases, including the PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wanfang, and Chinese Science and Technology Periodical (VIP) databases, from their inception to January 15, 2021. All statistical analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Broad areas of disagreement also exist regarding the choice to stimulate one or both hemispheres in stroke patients. Some authors showed greater clinical efficacy of bilateral stimulation [86,96 && ], whilst others did not find significant differences [97,102], or found that the unilateral stimulation of the ipsilesional [104 && ] or contralesional [98] hemisphere might be more effective in patients with unilateral hemispheric stroke. Finally, findings by Xie et al [103] suggested that both bilateral stimulation and unilateral stimulation of the contralesional hemisphere, but not stimulation of the ipsilesional hemisphere, could induce improvement of dysphagia.…”
Section: Noninvasive Brain Stimulation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad areas of disagreement also exist regarding the choice to stimulate one or both hemispheres in stroke patients. Some authors showed greater clinical efficacy of bilateral stimulation [86,96 && ], whilst others did not find significant differences [97,102], or found that the unilateral stimulation of the ipsilesional [104 && ] or contralesional [98] hemisphere might be more effective in patients with unilateral hemispheric stroke. Finally, findings by Xie et al [103] suggested that both bilateral stimulation and unilateral stimulation of the contralesional hemisphere, but not stimulation of the ipsilesional hemisphere, could induce improvement of dysphagia.…”
Section: Noninvasive Brain Stimulation Techniquesmentioning
confidence: 99%
“…The efficacy of NIBS may be greater in the acute/subacute phases of stroke, when neuroplasticity is highly expressed [98,99 ▪▪ ]; however, a recent review showed that tDCS improved swallowing function in the chronic stage but not when applied during the first 2 weeks after stroke [104 ▪▪ ], which may be imputable to the low number of studies focusing on the acute stroke phase.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Given the growing interest in tDCS and the mixed findings in this area, several systematic reviews and meta-analyses have evaluated its clinical efficacy for PSD in the recent 2 years [35,36,[98][99][100]. Collectively, these reviews showed that tDCS has modest but promising beneficial effects for this population.…”
Section: Stroke Studiesmentioning
confidence: 99%
“…tDCS is one of the NIBS modalities that can affect cortical excitability through modulation of neural activity using weak electrical currents [ 9 , 10 ], and has shown effectiveness in post-stroke dysphagia treatment [ 10 ]. However, the effects of tDCS may vary depending on the attentive level of the participant, detection of the motor hot spot, and also on the intrinsic factors such as age, gender, cortical thickness, or genes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%